Teaching as Service in Knowledge Work - Tan, Betsy Joy B. (Silliman Journal, 2022)
Effective schools literature is already replete with theories on the indispensable partnership between teachers and students. However, the literature on knowledge as the reality and truth of such partnership has not been acknowledged as assertively as the ownership of land, the wealth in the Agricultural Age; and the ownership of capital, the wealth in the Industrial Age. This paper asserts that ownership of knowledge as the wealth in today’s Knowledge Age has not been emphasized in many classrooms particularly in the Philippines where a) vulnerable knowledge work situations may result because of a mismatch between knowledge gained in school and essential knowledge for job entry; b) mass media such as television greatly impacts the society; and c) content specialists teaching in tertiary institutions may not have the needed training in teacher education. Moreover, this paper discusses how this concern may be addressed by a school’s teacher evaluation program, and in this context identifies the roles and the rights of the school and the teacher in helping create an environment where knowledge work is effectively and efficiently facilitated.